Chování funkcí více proměnných z hlediska extrémů - Beseda, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2015)
Problematika extrémů funkce více proměnných spočívá ve výpočtu maxima nebo minima této funkce. Toto maximum a minimum funkce může být lokální, vázané nebo globální. K zjištění extrémů využíváme zejména Sylvestrovo kritérium, pomocí kterého vyšetřujeme chování funkce v stacionárních bodech. Stacionární bod je bodem, ve kterém předpokládáme existenci maxima či minima funkce.

Thesis deals with problems of extreme searching in multivariable calculus. Searching maxima/minima of the function can be moreover specified to local extremes, global extremes or strict extremes. For finding extremes we use Sylvester's criterion, which helps us investigate the behavior of functions in stationary points. Stationary point is point, where maxima or minima of the function is expected.
The behavior of functions of several variables in terms of extremes
Keywords: Extrémy funkce; maximum a minimum; Extremes of functions; maximum and minimum